Retention of knowledge about basic cardiac-pulmonary resuscitation in medical students. Cienfuegos (2017-2018) - Victor Rene Navarro Machado; Niurys González Cano; Arelys Falcón Hernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Introduction: knowledge retention at medium and long term in cardiac-pulmonary resuscitation is a problem in education systems worldwide. Objective: to determine the level of knowledge retention about basic cardiac-pulmonary resuscitation in medical students. Method: prospective longitudinal research; developed at the University of Medical Sciences Cienfuegos. An exam was applied to 377 first year medical students about cardiac-pulmonary resuscitation after a 20 hour theoretical-practical course in December 2017. A year later, to a sample of 185 ( simple random, level of confidence 95% and error margin of 5%) the same exam is repeated. Global and particular results are compared according to the initial marking. Results: In the first exam(2017) the general number of students who passed was 80.4%, from it with a degree of quality (good and excellent) 50.66%. A year later, these figures decreased to 46.5 and 14.1 % respectively. The percentages of ratings was also qualitatively lower in 2018 for each group than those obtained in 2017. The worsts ( fair and poor) in 2018 are not related to the rating obtained in 2017. The evaluation of the teaching process to the students and teachers was good. Conclusion: the level of knowledge retention about Basic cardiac-pulmonary resuscitation at a year time is low, independently to the ratings obtained in 2017. The quality of the teaching process was adequate and seems not to influence these results.